Latent entrepreneurship in transition economies - Hilal Atasoy (IZA World of Labor, 2015)
Because entrepreneurial activity can stimulate job creation and long-term economic growth, promoting entrepreneurship is an important goal. However, many financial, bureaucratic, and social barriers can short-circuit the process of actually starting a business, especially in transition economies that lack established institutional systems and markets. The main obstacles are underdeveloped financial markets, perceptions of administrative complexity, political and economic instability, and lack of trust in institutions. Gender disparities in the labor market are also reflected in less entrepreneurial activity among women than men.
Keywords: L26; P2; 330; latent entrepreneurship; attempted entrepreneurship; self-employment